Misi Dan Pelayanan Sosial: Jejak Badan Zending RMG Di Tanah Batak (1861-1940) - Samosir, Jetti (Sekolah Tinggi Diakones HKBP, 2024)
The mission and social services carried out by missionaries in the Batak Land in the 19th century have had a significant impact on the Batak people. Mission and social services are intertwined. From the outset, missionary activities have been closely linked to the development of Batak community infrastructure, including churches, hospitals, educational facilities, and the economy, often referred to as